Effect of contact geometry on the friction of acrylamide hydrogels with different surface structures - Liu, Wenrui; Simič, Rok; Liu, Yuhong; Spencer, Nicholas D. (Friction, 2022)
Polyacrylamide (PAAm) hydrogels with brush-covered or crosslinked surfaces were produced and their tribological behavior was studied over a wide range of sliding speeds for two different contact geometries: sphere-on-flat and flat-pin-on-flat. Irrespective of the contact geometry, the brushy hydrogel surfaces displayed up to an order of magnitude lower coefficients of friction μ (COF) compared to the crosslinked surfaces, even achieving superlubricity ( μ < 0.01). In general, a hydrogel sphere showed a lower coefficient of friction than a flat hydrogel pin at a similar contact pressure over the entire range of sliding speeds. However, after normalizing the friction force by the contact area, the shear stress of hydrogels with either crosslinked or brushy surfaces was found to be similar for both contact geometries at low speeds, indicating that hydrogel friction is unaffected by the contact geometry at these speeds. At high sliding speeds, the shear stress was found to be lower for a sphere-on-flat configuration compared to a flat-pin-on-flat configuration. This can be attributed to the larger equivalent hydrodynamic thickness due to the convergent inlet zone ahead of the sphere-on-flat contact, which presumably enhances the water supply in the contact, promotes rehydration, and thus reduces the friction at high sliding speeds compared to that measured for the flat-pin-on-flat contact.